Social Services for Neglected Elderly at Tresna Werdha Harapan Ibu Social Institution in Semarang City - Ria Faisyahril; Dini Andriani; Eka Nurwahyuliningsih (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
Social services for neglected elderly at the Harapan Ibu Social Institution for the Elderly (Panti Sosial Tresna Werdha Harapan Ibu) include decent shelter, health care and guidance, livelihood security, development of potential and skills, creative activities, and spiritual guidance. The purpose of this study is to examine: 1) the characteristics of the informants, and 2) the identification of the types of social services for neglected elderly at the Harapan Ibu Social Institution for the Elderly. The method used is qualitative research. The data sources consist of primary and secondary data. Data collection techniques include in-depth interviews with four informants, participatory observation, and documentation study. The research results were then analyzed using qualitative analysis techniques. The techniques for testing data validity include credibility, dependability, and confirmability tests. The aspects of social services examined include social security, housing, health, education, and personal social services. The findings of this study illustrate that the services provided at the Harapan Ibu Social Institution for the Elderly in Semarang City have fulfilled the aspects of social services for the elderly.Keywords : Social Services, Social Welfare, Neglected Elderly and Tresna Werdha Social Institution